2018
DOI: 10.17135/jdhs.2018.18.2.105
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Number of Brushing Strokes in Toothbrushing Education

Abstract: The purpose of this study was to focus on the number of brushing strokes among the performance factors and identify if the 10 times stroke of the rolling method is rational. Moreover, we evaluated the changes in oral health knowledge, perception, and behavior after our rolling method instruction. The 10-stroke method of toothbrushing has been regarded as an effective method of removal of dental plaque, although there is little evidence to support this claim. We allocated 40 healthy subjects to two intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
4
0
2
Order By: Relevance
“…Sikat gigi merupakan metode self-care mekanis yang paling umum digunakan terutama untuk membersihkan plak. 37 Penyuluhan menyikat gigi merupakan bagian penting dari setiap program promosi kesehatan gigi dan mulut. 37,38 Tiga metode yang dapat dilakukan untuk promosi kesehatan gigi dan mulut adalah metode verbal, tertulis serta audiovisual.…”
Section: Pembahasanunclassified
See 1 more Smart Citation
“…Sikat gigi merupakan metode self-care mekanis yang paling umum digunakan terutama untuk membersihkan plak. 37 Penyuluhan menyikat gigi merupakan bagian penting dari setiap program promosi kesehatan gigi dan mulut. 37,38 Tiga metode yang dapat dilakukan untuk promosi kesehatan gigi dan mulut adalah metode verbal, tertulis serta audiovisual.…”
Section: Pembahasanunclassified
“…37 Penyuluhan menyikat gigi merupakan bagian penting dari setiap program promosi kesehatan gigi dan mulut. 37,38 Tiga metode yang dapat dilakukan untuk promosi kesehatan gigi dan mulut adalah metode verbal, tertulis serta audiovisual. 39 Semakin dini anak mendapatkan intervensi pendidikan kesehatan gigi dan mulut yang baik dari ibu, maka semakin baik tingkat kesehatan gigi dan mulut anak.…”
Section: Pembahasanunclassified
“…This test measured the number of brushing strokes that the varnish could resist being mechanically removed by tooth brushing. Prior studies found that 20 brushing strokes (10 strokes/area for tooth brushing with tooth brushing being performed twice a day) are equal to the effective daily number of brushing strokes to brush a specific tooth area usually recommended by dentists 24,25) . The average human brushing force is 1.6±0.…”
Section: Brushing Testmentioning
confidence: 99%
“…The results of the brushing test indicated that the cyanoacrylate varnish had a significantly better abrasion resistance compared with Duraphat varnish. The Duraphat varnish was easily removed by abrasion as demonstrated by no residual Duraphat varnish being present on the tooth surface in all groups after brushing, including the 20 brushing stroke group, which is considered a small number of brushing strokes and equivalent to one day of brushing 24,25) .…”
Section: Brushing Testmentioning
confidence: 99%
“…It is, therefore, necessary to periodically remove bacteria from the teeth or tongue in the mouth, and one of the most common and effective methods for this is tooth brushing 1) . Although a toothbrush is the most common oral hygiene care tool and is effectively utilized to prevent oral diseases by removing dental plaque in the oral cavity 2) , it can become easily contaminated with microorganisms, blood, saliva, and oral tissue shed in the oral cavity 3) . Moreover, toothbrushes are often stored in an environment where bacteria, fungi, or yeast are present.…”
Section: Introductionmentioning
confidence: 99%